2007
DOI: 10.1073/pnas.0610125104
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis between catechol- O -methyltransferase and type II metabotropic glutamate receptor 3 genes on working memory brain function

Abstract: Dopaminergic and glutamatergic systems are critical components responsible for prefrontal signal-to-noise tuning in working memory. Recent functional MRI (fMRI) studies of genetic variation in these systems in catechol-O-methyltransferase (COMT) and in metabotropic glutamate receptor mgluR3 (GRM3), respectively, suggest that these genes influence prefrontal physiological signalto-noise in humans. Here, using fMRI, we extend these individual gene findings to examine the combined effects of COMT and GRM3 on diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
151
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 70 publications
13
151
1
3
Order By: Relevance
“…Relevant to this investigation are studies that have begun to shed light on the epitasis between COMT and other genes in the context of phenotypes such as novelty seeking (Benjamin et al, 2000), extraversion (Golimbet, Alfimova, Gritsenko, & Ebstein, 2007) and the stress response (Jabbi et al, 2007). Moreover, a recent functional magnetic resonance imaging study of working memory revealed that the COMT Met homozygous genotype mediated against inefficient task related brain activations observed in the combined presence of glutamate receptor mgluR3 (GRM3) and the homozygous COMT Val genotype (Tan et al, 2007). Future studies should examine whether interactions between COMT and other genes that affect dopamine catabolism and other neurotransmitter systems influence gait in young and old individuals as well as in disease states where gait and executive functions become impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this investigation are studies that have begun to shed light on the epitasis between COMT and other genes in the context of phenotypes such as novelty seeking (Benjamin et al, 2000), extraversion (Golimbet, Alfimova, Gritsenko, & Ebstein, 2007) and the stress response (Jabbi et al, 2007). Moreover, a recent functional magnetic resonance imaging study of working memory revealed that the COMT Met homozygous genotype mediated against inefficient task related brain activations observed in the combined presence of glutamate receptor mgluR3 (GRM3) and the homozygous COMT Val genotype (Tan et al, 2007). Future studies should examine whether interactions between COMT and other genes that affect dopamine catabolism and other neurotransmitter systems influence gait in young and old individuals as well as in disease states where gait and executive functions become impaired.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 These neurotransmitter systems and related candidate genes have also been implicated in schizophrenia, 40 but the mechanism by which genetic susceptibility impacts human brain function has been obscure. Neuroimaging genetics is a promising research strategy for elucidating such mechanisms, 22 and the effect of genetic variation on these component brain systems, including epistatic interactions of genes regulating various neurotransmitter systems, 41,42 has begun to translate genetic risk into systems neuroscience.…”
Section: Are Intermediate Phenotypes Intermediate In Terms Of Diseasementioning
confidence: 99%
“…In the actual study, 47 the SNP showing the strongest clinical association was also associated with several cognitive measures and several imaging phenotypes related to the known biology of the gene, including epistasis with dopaminergic modulation. 42 Further research will be needed to refine the statistical parameters by which combinations of disease-association and intermediate phenotype tests could be extended to more genes. But it would appear that multi-staged nested strategies can be designed such that combinations of hypothesis-driven tests of sufficient power, when integrated, will give reasonably low overall false-positive call rates, while offering insights into human disease mechanisms.…”
Section: A Comment On Controlling For Statistical Errormentioning
confidence: 99%
“…A possible reason for these inconsistent results is that complex cognitive functions such as episodic memory are influenced by multiple genes (Lindenberger et al, 2008;McClearn, 2006;Stelzel, Basten, Montag, Reuter, & Fiebach, 2009;Tan et al, 2007;Yacubian et al, 2007). Therefore, the effect of a single gene likely depends on the background effects of other interacting genetic modifiers.…”
Section: Introductionmentioning
confidence: 99%